RECOGNISING EMOTIONAL ABUSE AND MOBBING IN ADOLESCENTS: CAUSES AND IMPACTS - Jurs, Pāvels; Ročāne, Maija; Kulberga, Inta; Striguna, Santa; Titrek, Osman (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Emotional abuse can cause severe effects on person`s emotional development, e.g., sense of worthlessness, wearing away confidence and self-esteem, anxiety, depression, etc. Psycho-emotional wellbeing becomes essential for the adolescent to become successful at school, which can be reached through emotional support, understanding and self-discovery. Emotional abuse quite often is not recognized, because of possible judgement from family, friends, teachers and community members. Silence about emotional and physical abuse can be the result of fears and emotional abuse situations which can seem as normal for the victim. Therefore, the first step to solve mental problems is becoming aware of a problem and reducing stigma about mental health. Survey results highlight the need for parents to improve their knowledge, attitudes and skills about emotional abuse and understanding of how to communicate with their children about possible emotional abuse situations at schools. Survey results also highlight that one of the main reasons why mobbing occurs is students` attitude towards difference of others e.g. different interests, lifestyle, appearance, clothes, way of communication, sexual orientation, etc.). Using theoretical and empirical research (survey) methods, the aim of the article is: to describe forms of emotional abuse, highlighting the link between emotional abuse and physical abuse and the impact of it on the emotional well-being of adolescent at school. The authors of the article have identified the main problems faced by students, teachers and parents in cases of emotional abuse.